KEMAMPUAN MEMBAYAR PENUMPANG TERHADAP TARIF KAPAL CEPAT DAN KAPAL LAMBAT JALUR PENYEBERANGAN KE KOTA SABANG - Arini Arini; Renni Anggraini; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Transport aims to provide the public with a service of mobility or mobility that is affordable to purchase and creates a condition of transportation services that is safe, convenient, fast, smooth, orderly, reliable and competitive, sea transport plays an important role in every activity, indeed are in the waters. This study aims to analyze the characteristics of users of fast and slow ship transportation services, analyze the ability to pay (ATP) based on the allocation of income. From the research results obtained Ability To Pay (ATP) fast ship of Rp. 42.284, - with an ideal rate of Rp. 56,367, - and still require subsidy of Rp. 37.716, - while for aboard slow ship Ability To Pay (ATP) of Rp. 16.660, - with an ideal rate of Rp. 22,995, - and still require a subsidy Rp. 10,340,- When compared to tariffs, all respondents (100%) of ATP values are well below the official tariff rates. The value of ATP obtained is lower than the official tariff required for subsidies, for fast vessels and slow vessels it is not possible to increase tariff rates. Average value / mean level of fast ship service including good category and for slow ship enter very good service category